The association of compassion fatigue with the tendency to drop out among hospice volunteers: The association of compassion fatigue with the tendency to drop out among hospice volunteers (Paliativní medicína, 2025)
IntroductionMost volunteers in hospice services mention that their work brings them joy and a sense of purpose. However, volunteer work also has its challenges, such as an unclear role within the palliative team, limited authority, helplessness, and negative emotions associated with death and dying. The aim of this study was to determine whether these potential negative aspects of volunteer work are reflected in concepts such as compassion fatigue and compassion satisfaction, and whether they further influence volunteers' decision to leave the services.MethodsWe conducted a cross-sectional questionnaire survey among volunteers in hospice facilities in the Czech Republic from November 18, 2023, to February 9, 2024. The study included active volunteers from both inpatient and mobile hospice services who were actively engaged with patients. The main objective of the analysis was to examine whether compassion fatigue and compassion satisfaction have any connection with the tendency of volunteers to leave hospice services. Another goal was to determine the levels of compassion satisfaction and compassion fatigue among volunteers within the mentioned constructs.ResultsDuring the specified period, 88 respondents from 8 different regions of the Czech Republic filled out the questionnaire. The resulting scores for compassion satisfaction and compassion fatigue were generally positive. Similarly, the score for the tendency to leave was positive. A low to moderate negative correlation was found between compassion satisfaction and the tendency to leave.
Keywords: palliative care; hospice care; volunteering; compassion satisfaction; compassion fatigue